Pushover analysis of confined masonry walls using a 3D macro-modelling approach. (15th December 2019) - Yacila, Jhair; Camata, Guido; Salsavilca, Jhoselyn; Tarque, Nicola
Highlights: A 3D macro-modelling approach is proposed to study confined masonry walls (CMW). A dynamic explicit solver can be properly used to solve quasi-static problems. Experimental outcomes of masonry should not be used directly for a macro-model. The nonlinear behavior of CMW is strongly influenced by masonry's tensile properties. Abstract: This paper shows a novelty way to simulate the nonlinear behaviour of confined masonry walls subjected to in-plane lateral loading by using a 3D macro-modelling approach. For this purpose, the finite elements method implemented in ABAQUS software was used. All the 3D solid finite elements were modelled as a single part, which allowed avoiding modelling the contact interfaces between concrete and masonry elements. The nonlinear behaviour of the concrete and masonry were governed by two main types of failures: crushing and cracking, which were properly represented by the Concrete Damage Plasticity (CDP) model. Steel rebars were modelled as elastic–plastic with hardening and were assumed to have a perfect adhesion with the surrounding concrete by means of the embedded constraint. Prior to the modelling process, experiments were carried out whose results were used as patterns to validate the proposed model. A calibration process of the tensile properties of masonry was conducted for properly fitting the experimental patterns. As a result, there were good agreements between the numerical and experimental outcomes in terms of capacity curves and cracking patterns.